Body Image Representation in MS Glow for Men Advertising; An Analysis of Circuit of Culture - Bahtiar, Jessica Yunanda; Rahayu, Mundi (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
This study discusses an advertising video of “MS Glow for Men” starring Babe Cabita and Marshel, which is intended as an encouragement for people to promote self-acceptance and break the myth of beauty of light skin and a perfect body. This study aims to answer the questions of how advertising was created, distributed, consumed, or perceived by the public and seek the explanation of how the body image represented in MS Glow for Men advertising. The researchers answer the question by applying Stuart Hall’s framework of the circuit of culture that covers five aspects: regulation, production, identity, consumption, and representation. The study shows that the advertising contains a message that the standardization of beauty should cover all types of body image and physical appearance by representing the idea that anyone can become an ambassador of the beauty brand just like Babe Capita and Marshal. The visual text shows that the advertisement influences the audience in building a perception of the ‘beauty’ through the visual image of the advertisement which presents a more realistic notion of beauty.